REKONSTRUKSI BUDAYA HAKIM PADA PENEGAKAN HUKUM PIDANA DALAM KONTEKS SISKUMNAS/BANGKUMNAS - dewi, erna (JURNAL KOMPILASI)
Judge as a party breaker case is very important as a determinant of future laws, because every decision of the judge will become the center of public attention, and therefore the judges not only act as mouthpiece of the law, but judge also acted as the finder of law (recht finding), in accordance with the values cultural values that live in the community, especially the values of pancasila. Cultural reconstruction of judges in criminal law enforcement in the context siskumnas / bakumnas need to be based on the values of pancasila as the national legal guidelines as well as local wisdom in order to realize justice pancasila, especially, religious values, humanistic and social justice.